2005
DOI: 10.2174/1573397054023182
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Specificity and Clinical Relevance of Antiphospholipid Syndrome- Related Autoantibodies

Abstract: The presence of antiphospholipid antibodies (aPL) combined with venous or arterial thrombosis, and/or obstetric complications defines the antiphospholipid syndrome (APS). Lupus anticoagulants (LA) and anticardiolipin antibodies (aCL) were the first described aPL. It has been shown that aPL, despite their name, are not directed against anionic phospholipids, as had previously thought, but are a part of a large family of autoantibodies against phospholipid-binding plasma proteins. The most important and relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 104 publications
0
14
0
1
Order By: Relevance
“…The primary inhibitor of FVIIa/TF is tissue factor pathway inhibitor (TFPI). Interestingly, previous studies have shown that antithrombin (AT) inhibits FVIIa and FVIIa/ TF in the presence of heparin [1][2][3][4][5]. However, only limited information is known about the role of other serine protease inhibitors (Serpins) in regulating FVIIa and FVIIa/TF activity.…”
Section: Disclosure Of Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary inhibitor of FVIIa/TF is tissue factor pathway inhibitor (TFPI). Interestingly, previous studies have shown that antithrombin (AT) inhibits FVIIa and FVIIa/ TF in the presence of heparin [1][2][3][4][5]. However, only limited information is known about the role of other serine protease inhibitors (Serpins) in regulating FVIIa and FVIIa/TF activity.…”
Section: Disclosure Of Conflict Of Interestmentioning
confidence: 99%
“…The APS-associated aPL are autoantibodies directed against b 2 glycoprotein I (anti-b 2 GPI) and prothrombin [2]. aPL are also found to be positive in patients with viral as well as bacterial infections.…”
mentioning
confidence: 99%
“…Considering anti 2 GPI, it was early described an association between the presence of these antibodies and thrombosis [86] and it is well known that they correlated very well with clinical manifestations of APS [6,9,23,87]. For this reason anti 2 GPI were included in the revised criteria for APS [1].…”
Section: Anti 2 Gpi Testingmentioning
confidence: 99%
“…The other protein that has been recognized as a protein antigen involved in APS is human prothrombin (PT) [5]. Many other proteins with high affinity for PL have been found to be recognized by serum of many patients with APS: Annexin A5, Protein S, TFPI, etc, but these assays have not become clinical useful [6].…”
Section: Introductionmentioning
confidence: 99%
“…В то же время ИАП 1 является белком острой фазы, отмечалось повыше-ние его содержания в острый период инфаркта миокарда, при сепсисе и воспалительных заболеваниях [14,15]. Во всех исследованиях, проводимых в данной области, бы-ло показано, что у пациентов с СКВ и ВА активность ИАП 1 значительно повышена [16,17].…”
unclassified